Constrictive pericarditis diagnosed following liver transplantation - ŞAYLAN ÇEVİK, BERNA; TUTAR, ENGİN; AKALIN, FİGEN (MARMARA UNIV, FAC MEDICINE, 2021)
Constrictive pericarditis is frequently diagnosed during evaluation of the patients for hepatosplenomegaly and easily missed if not considered in differential diagnosis. Herein, we present a patient diagnosed with constrictive pericarditis during his investigation for impaired liver functions and right heart failure one year after liver transplantation. A thirteen-year-old boy presented with abdominal distention, dyspnea and fatigue. He had undergone liver transplantation due to liver failure in the previous year, and the symptoms had recurred in the last three months. Physical examination revealed normal heart sounds. Abdominal distention and ascites were present. Cardiothoracic index and pulmonary vascular markings were normal on chest X-ray. Echocardiography showed biatrial dilatation. Thickening of the pericardium with calcifications was demonstrated by thorax computerised tomography. High pulmonary wedge pressure and equalization of end-diastolic pressures were found during catheter-angiography. Pericardiectomy was performed, histopathology was compatible with chronic fibrinous pericarditis. The patient improved dramatically after surgery, the right heart failure findings resolved, and the liver graft functions turned to be normal. Constrictive pericarditis must be considered in differential diagnosis of hepatosplenomegaly, liver dysfunction and right heart failure since surgical treatment is possible and lifesaving.
Keywords: Constrictive pericarditis; Echocardiography; Liver transplantation; Pericardiectomy; MODERN-ERA; ASCITES; IMPACT